Comparative Analysis of the Impact of Volleyball on Physical Fitness Improvement in Male and Female Students of the Communication Science Program at UPN Veteran Yogyakarta - Sumintarsih, Sumintarsih; Saptono, Tri; Mustofa, Hanafi (Jurnal Indonesia Sosial Sains, 2024)
Research objectives the effect of volleyball games on improving the physical fitness of male students. The effect of volleyball games on improving the physical fitness of female students. The difference in the effect of volleyball games between male and female students on improving physical fitness. This research an uses experimental method. The population of this research were students of the Communication Science Study Program of UPN "Veteran" Yogyakarta in the academic year 2023/2024 who were taking the Sports II course in volleyball. The data analysis method of this study uses the t-test. Test your data analysis requirements using normality and homogeneity tests. Research Results: 1) The average effect of volleyball games on increasing the physical fitness of male students is 2.431666667. 2) The average effect of volleyball games on the physical fitness of female students is 3.001666667. 3) The difference in the effect of volleyball games on improving physical fitness between male and female students is an average difference of 0.57.